THE DEVELOPMENT OF SHARIA ECONOMIC LAW IN THE CONSTELLATION OF INDONESIAN NATIONAL LAW - Wiwin Sutoyo; Luthfi Hamidi; Nurinawati Kurnianingsih (JOURNAL EQUITABLE, 2024)
Islamic law is a living law that operates in the midst of society. Thus, Islamic law is a law that cannot be separated from Indonesian society, to build an economic system that is in accordance with existing norms and traditions. Starting in the 1940s and decades later, the concept of Sharia Economic Law began to emerge in various countries. The very high growth of sharia economic practices, sharia economic law legislation in Indonesia was born as a logical consequence of the dialogue and intersection of Islamic teachings with the social environment. Therefore, the formulation, characteristics and expression of sharia economic law legislation is realized by the diversity of local values (local policies) that surround the growth of sharia economic law. The historical development of sharia economic law legislation in Indonesia displays a dynamic character that is uniquely Indonesian. Socio-political and cultural values are important elements that influence the pace and direction of sharia economic law legislation in Indonesia. This article proves that Islamic economic law has appeared as a sub-system in the Indonesian national legal order with the birth of various instruments in the formation of laws. . law, as Indonesian national law.